0.45‐V 5.4‐nW switched‐capacitor bandgap reference with intermittent operation and improved supply immunity. Issue 20 (1st October 2018) - Luo, Ziyang; Lu, Yan; Martins, Rui P.
Abstract : Switched‐capacitor networks have been used as bandgap references (BGRs) to replace the area‐consuming resistors in ultra‐low power applications, incorporated with voltage doubler (2X) charge pumps to operate at low supply voltages. However, the open‐loop charge pumps are sensitive to supply and load variations. Therefore, in this work, constant bias currents are added to the cross‐coupled 2X charge pumps to reduce the supply sensitivity, and also to reduce the output ripples without using large capacitors. To further reduce the power consumption, a low‐leakage sample and hold (S&H) circuit is used for an intermittent operation, the active/idle duty ratio of the BGR core is 1/15. Designed in standard 65 nm CMOS, the proposed BGR reaches a temperature coefficient of 64 ppm/°C consuming only 5.4 nW with a minimum supply of 0.45 V (simulated).